Accurate PD-L1 Protocols for Non–Small Cell Lung Cancer can be Developed for Automated Staining Platforms With Clone 22C3. Issue 6 (July 2017) - Røge, Rasmus; Vyberg, Mogens; Nielsen, Søren
Abstract : Treatment using immunotherapy against PD-L1 or PD-1 has become one of the hottest topics in Pathology and Oncology. Correct selection of patients eligible for treatment requires optimal immunohistochemical staining protocols. Treatment with pembrolizumab requires diagnostic examination of the patient's tumour using the companion diagnostic Ready-To-Use pharmDx kit from Dako Agilent based on the mAb 22C3 clone on the Autostainer platform. However, not all diagnostic pathology labs have access to this staining platform. This purpose of this study was to develop and validate protocols for PD-L1 detection for all major staining platforms using the concentrated format of 22C3 that would give similar staining result (equal Tumour Proportion Scores) to the pharmDx kit.